2007
DOI: 10.3748/wjg.v13.i42.5654
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing cirrhosis is associated with increased mortality of traumatic patients: Analysis of cases from a trauma center in East China

Abstract: AIM:To determine the impact of cirrhosis on trauma patients and define the factors predicting death. METHODS:The data on patients admitted to the trauma center from January 2000-2005 were studied retrospectively. The clinical variables were recorded and compared to identify the factors differentiating cirrhotic trauma survivors from non survivors. Child's classification criteria were derived from the reviewed charts of cirrhotic trauma patients to evaluate their predictive value in cirrhotic trauma. Trauma reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Although the increased risk for adverse outcomes in cirrhotic patients after injury has been well documented, [6][7][8][9][10][11][12][13][14][15] the effect of liver failure on outcomes in patients with TBI, however, has not yet been examined. The present study, based on a cohort of isolated head injured trauma patients, found a significantly increased overall mortality rate at 34 per cent among cirrhotic TBI patients compared with a rate of 18.1 per cent in their noncirrhotic counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the increased risk for adverse outcomes in cirrhotic patients after injury has been well documented, [6][7][8][9][10][11][12][13][14][15] the effect of liver failure on outcomes in patients with TBI, however, has not yet been examined. The present study, based on a cohort of isolated head injured trauma patients, found a significantly increased overall mortality rate at 34 per cent among cirrhotic TBI patients compared with a rate of 18.1 per cent in their noncirrhotic counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…L IVER CIRRHOSIS has been identified as a significant risk factor for both morbidity and mortality in elective [1][2][3][4][5] and in emergently ill surgical patients. [6][7][8][9][10][11][12][13][14][15] In a previous investigation from our institution, cirrhotic trauma patients undergoing laparotomy had an almost three-fold increased risk of developing severe complications and a seven-fold increased risk of death compared with a matched cohort of noncirrhotic trauma victims requiring emergent abdominal surgery. 6 In patients with traumatic brain injury (TBI), however, no studies exist documenting the impact of liver cirrhosis on their in-hospital outcomes.…”
mentioning
confidence: 99%